Impulse Effect of The Flood on The Livelihoods of Marine Fishers in Kerala - Shyam. S. Salim; Athira. N.R; Harsha Elizabeth James; Monolisha S; Smitha R.X; Shinu A.M. (Journal of Indian Fisheries Association, 2020)
The devastated flood that ravaged Kerala had pegged the loss in the livelihood of fishermen incurring damage to craft, gear and other fishing accessories. The total loss due to damage or washing away of crafts, gear and engine was Rs 6.72 crores in inland and Rs 4.24 crores in the marine fisheries sector. Amidst the fishers lost considerable employment and unrealised wages due to flood and their involvement in the rescue operations. A study was conducted to assess the impulse eﬀect of the flood on the livelihoods of marine fishers in Kerala with special focus on analysing the role played by the fishermen in the relief activities which could result in streamlining more policies and measures to enhance the livelihood of fisher community as well as mitigating flood in future. The results revealed that an average of 2- 4 week’s employment days of the fishers have been lost due to flood and alternative livelihood options of the fishermen have also been aﬀected with the highest average loss incurred for fish farming (45.45 per cent). The study suggested imparting training to fishers as one of the appropriate method for mitigating flood or other natural hazards in future owing to fisher’s proximity to nature and their rich fishing experience. However, for confronting the impending disasters and to get rid of from the future havocs, appropriate proactive policies and action plans should be developed with the proactive participation of stakeholders.